The public loneliness of endurance athletes: Creating ambient affiliation through involvement strategies on Twitter. (April 2020) - Tovares, Alla V.
Highlights: Athletes mobilize various linguistic strategies to create ambient affiliation. Athletes use detail and imagery to maintain involvement with the audience online. The features of online platforms and parameters of sports shape athletes' tweets. Twitter redefines what it means to be endurance athletes practicing solitary sports. Abstract: The accessibility and interactivity of Twitter both facilitate athlete-fan interaction and contribute to the time/space compression between sporting events and communication about them. While numerous studies investigate real-time participatory engagement of fans on Twitter, athletes' use of Twitter during competition remains underexplored. Using a case study approach, this study brings together computer-mediated discourse analysis and prior work on involvement in discourse to examine tweets posted during competitive events by two endurance athletes (an experienced amateur marathon runner and an elite rock climber). Specifically, it explores how athletes mobilize various linguistic strategies to create relations of connectedness, or ambient affiliation (Zappavigna, 2011), with their respective audiences who are distanced spatially and often temporally. It also demonstrates how the affordances and limitations of technology, and the constraints of the athletic events themselves, shape ambient involvement. In this way, this work adds to our understanding of how ambient affiliation is constructed in a particular context – a competitive athletic event of an endurance athlete practicing a solitary sport – while also shedding light on how involvement is created and maintained with a largely unknown online audience.